Description of the Siege of Jajce in 1464 by Kritoboulos (Prilozi za orijentalnu filologiju, 2017)
The article presents the Croatian translation of a fragment from the History of Muhammad the Conqueror (Mehmet II) by Kritoboulos, relating to the siege of Jajce in 1464. The manuscript of the French translation from the 19th century has been preserved in the Archives of the Croatian Academy of Sciences and Arts in Zagreb. Michael Kritoboulos (15th century), a Byzantine historian and a historian of the Ottoman Empire, from 1436 to 1466 governor of Imbros (today's Turkish island of Imroz), in 1456 was appointed vice-regent by the sultan Muhammad the Conqueror. Kritobulos describes the raids of Muhammad the Conqueror in Bosnia and the ruin of the Bosnian State. The part of the text relative to the fall of Bosnia is also relevant to some events associated with the siege of Jajce in 1464.